Pemberian Motivasi Berprestasi di dalam Usaha Peningkatan Kinerja Sumber Daya Aparatur Sipil Negara - Alfiandri, Alfiandri (Jurnal Ilmu Administrasi Negara (JUAN), 2015)
Pemberian Motivasi Berprestasi Di Dalam Usaha Peningkatan KinerjaSumber Daya Aparatur Sipil Negara Alfiandri(alfiandri@umrah.ac.id) (Jurusan Ilmu Administrasi Negara FISIP UMRAH) Abstract Motivation isan internalcondition ofa specificand directbehaviorto a goal. Achievementis an encouragementtoovercomeobstacles, carrypower,strugglingtodosomething difficultas well andas quickly aspossible. The achievement oforganizational goalscan not be separatedfromresources ownedbyan organizationwhich is drivenorrunemployeewhoplayed an active roleas an agent inpursuance of the objectivesof the organization. This paper aims todevelopthese issues inthe contemporaryto the dynamicsof scienceofPublic Administrationas anactivityaccountabilityacademic, specificallyto the study ofhuman resource development in public sector, bydoingstepassessingtheoreticallyandjuridicalagainst the granting ofachievement motivationinperformance improvementcivilianpersonnel resourcesof the country.This paperalsoisaresearchdone by studyingliterature study. Keywords : AchievementMotivation, EmployeePerformance, Organization.